2022
DOI: 10.3389/fmed.2022.914557
|View full text |Cite
|
Sign up to set email alerts
|

Serum Total Bilirubin With Hospital Survival in Adults During Extracorporeal Membrane Oxygenation

Abstract: BackgroundExtracorporeal membrane oxygenation (ECMO) is widely used for refractory cardiopulmonary failure treatment. The disadvantage of ECMO is its higher risk profile and clinical resource consumption. This observation examines the role of serum total bilirubin (TBIL) as a predictor of adult patient outcomes on ECMO support.MethodsThis retrospective observation reports a single-center experience with adults on ECMO support between 2018 and 2021. Data were collected regarding demographics, ECMO details, labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…However, increased bilirubin values before ECMO initiation was not associated with increased in-ICU mortality ( 6 ). ECMO-associated DHB was also associated with high mortality in children receiving ECMO support ( 8 ), as reported by Huang et al ( 9 ). Round-the-clock monitoring of serum bilirubin would therefore be beneficial for the precision management of patients receiving ECMO.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…However, increased bilirubin values before ECMO initiation was not associated with increased in-ICU mortality ( 6 ). ECMO-associated DHB was also associated with high mortality in children receiving ECMO support ( 8 ), as reported by Huang et al ( 9 ). Round-the-clock monitoring of serum bilirubin would therefore be beneficial for the precision management of patients receiving ECMO.…”
Section: Discussionmentioning
confidence: 55%
“…Advanced strategies for the management of liver failure, including artificial liver support systems, plasma exchange, and bilirubin adsorption, are gradually seeing increased usage in critically ill patients. Huang et al ( 9 ) showed that the SOFA score was potentially associated with hyperbilirubinemia occurrence after ECMO initiation, with a prediction accuracy of 0.800.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Kohs et al found that severe thrombocytopenia was associated with adverse outcomes in patients on ECMO [ 31 ]. Further authors have shown that serum bilirubin elevation was associated with an increased risk of in-hospital mortality after ECMO [ 32 ]. Likewise, Joo et al mentioned that total bilirubin ( p = 0.017), acute kidney injury ( p = 0.005) and dialysis ( p = 0.001) were predictors for adverse outcomes and were associated with higher mortality in patients on ECMO [ 33 ].…”
Section: Discussionmentioning
confidence: 99%